2018
DOI: 10.1080/17482631.2018.1479585
|View full text |Cite
|
Sign up to set email alerts
|

Listening to the screaming whisper: a voice of mother caregivers of children with autistic spectrum disorder (ASD)

Abstract: Purpose:This is a gap in knowledge related to leisure behaviours among mothers who have children with autistic spectrum disorder (ASD). This study intended to understand leisure behaviours associated with leisure constraints among these mother caregivers. Method: Using a series of semi- structured interviews, a total of 12 participants engaged in this study. Results: Our findings consisted of two sections: (1) leisure negotiation and (2) leisure constraints which are (a) a lack of time for themselves, (b) cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 33 publications
0
25
0
3
Order By: Relevance
“…First, the cross sectional nature of the study does not allow for making casual inferences and, with previous research reporting bi-directional relationships between CPB and caregivers' distress (Hutchison et al, 2016), longitudinal studies are needed to tease apart the direction of these effects. Second, by virtue of the recruitment method (i.e., online support groups), caregivers might have been fairly well supported, and this is not representative of the wider caregiving population (Kim et al, 2018). As such, and with social support predicting both CPB and benefit finding (Pakenham et al, 2004), findings reported here should be interpreted with a degree of caution.…”
Section: Discussionmentioning
confidence: 79%
“…First, the cross sectional nature of the study does not allow for making casual inferences and, with previous research reporting bi-directional relationships between CPB and caregivers' distress (Hutchison et al, 2016), longitudinal studies are needed to tease apart the direction of these effects. Second, by virtue of the recruitment method (i.e., online support groups), caregivers might have been fairly well supported, and this is not representative of the wider caregiving population (Kim et al, 2018). As such, and with social support predicting both CPB and benefit finding (Pakenham et al, 2004), findings reported here should be interpreted with a degree of caution.…”
Section: Discussionmentioning
confidence: 79%
“…A sobrecarga dessa rotina implica em acumulo de emoções que são reprimidas, sejam elas por insuficiente apoio social e familiar, dificuldades financeiras, fadiga emocional e física, os quais se enquadram em fatores de adoecimento para esses pais ou cuidadores. Sendo assim, uma das maiores estratégias de enfrentamento devido a possibilidade de extravasamento de sentimentos é a pratica de exercícios físicos (KIM et al, 2018).…”
Section: Qualidade De Vidaunclassified
“…Outras estratégias utilizadas são o lazer e interação social, como um alivio para o sofrimento psicológico, mas, isso acabava implicando em aparecimentos de sentimento de culpa, pois planejar algo sem a presença da criança tornavase uma transgressão em relação ao seu papel de protetor (KIM et al, 2018).…”
Section: Qualidade De Vidaunclassified
“…The informal caregivers of children have fewer social contacts and less time for themselves. Kim et al (2018) described that mother caregivers of children with special needs modified their leisure patterns in order to suit the desires and needs of the child. Murphy et al (2007) describe that feelings of lack of control and being in a state of preparedness cause stress for the informal caregivers of children.…”
Section: Well-being Of Informal Caregivers Of Children With Special Needsmentioning
confidence: 99%